2022
DOI: 10.1186/s43042-022-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of type 2 diabetes mellitus in Indian and Global Population: A Review

Abstract: Background Non-communicable diseases such as cardiovascular diseases, respiratory diseases and diabetes contribute to the majority of deaths in India. Public health programmes on non-communicable diseases (NCD) prevention primarily target the behavioural risk factors of the population. Hereditary is known as a risk factor for most NCDs, specifically, type 2 diabetes mellitus (T2DM), and hence, understanding of the genetic markers of T2DM may facilitate prevention, early case detection and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 88 publications
0
1
0
Order By: Relevance
“…This genetic diversity enhances the population's susceptibility to diabetes. 31 Environmental Factors and Urbanization: Rapid socioeconomic development and urbanization in India have led to changes in lifestyle. Factors such as altered diet, reduced physical activity, and higher income contribute to the increase in the incidence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic diversity enhances the population's susceptibility to diabetes. 31 Environmental Factors and Urbanization: Rapid socioeconomic development and urbanization in India have led to changes in lifestyle. Factors such as altered diet, reduced physical activity, and higher income contribute to the increase in the incidence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, genetics also plays a major role in increasing the prevalence of the disease. Several studies indicate that South Asians, in particular Asian Indians, are more susceptible to insulin resistance compared to other ethnic groups 2 , 4 , 5 . Even the migrant Indians living in different parts of the world were found to have higher diabetes rates 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In Lebanon, as of March 2, 2023, there were 1,232,063 confirmed cases of COVID-19, with 10,832 deaths (0.87% of total confirmed cases) [18]. Previous studies showed a positive link between COVID-19 infection and new-onset diabetes [19,20]. Since no previous studies tackling this topic were conducted in Lebanon, and little is known from an endocrinological point of view [12], the aim of this study was to identify a possible association between COVID-19 infection and new onset diabetes in a sample of Lebanese adults.…”
Section: Introductionmentioning
confidence: 99%